2021
DOI: 10.3390/ijerph18116138
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Riverbed Incision and Hydrological Evolution on Water Quality and Water Age Based on Numerical Simulation: A Case Study of the Minjiang Estuary

Abstract: In recent years, problems such as water quality deterioration, saltwater invasion, and low oxygen have appeared in estuaries all over the world. The Minjiang River in Fujian, as a typical tidal estuary area, is facing these thorny problems. In this paper, the effects of topography and hydrologic evolution on the water age and water quality of the lower reaches of the Minjiang River were simulated by building a hydrodynamic and water quality model. The results show that: (1) It was found that the riverbed incis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Additionally, studies confirmed increased soil contamination due to the mining of sand and stone, which is prevalent in the study area [19,20]. In particular, a high level of the extraction of sand, mainly through open pits in Minjiang estuary, was reported to negatively impact the eco-environment [21].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Additionally, studies confirmed increased soil contamination due to the mining of sand and stone, which is prevalent in the study area [19,20]. In particular, a high level of the extraction of sand, mainly through open pits in Minjiang estuary, was reported to negatively impact the eco-environment [21].…”
Section: Introductionsupporting
confidence: 54%
“…The soil is dominated by ferralsols, red and yellow soils of the humid tropics which are known for their iron-and aluminum-rich mineralogy [14,26,27]. The silt and clay soils eroded from the high mountain areas are mainly transported by rivers causing sedimentation in the lower reaches of the Minjiang river basin [21]. The natural vegetation of the area is predominantly south subtropical monsoon rain forest and evergreen broad-leaved forest [28].…”
Section: Study Area Location and Descriptionmentioning
confidence: 99%